Detection and Characterization of Quinone Outside Inhibitor-Resistant Phytophthora cactorum and P. nicotianae Causing Leather Rot in Florida Strawberry - Marin, Marcus V (Plant disease, 2022)
Phytophthora cactorum and P. nicotianae cause leather rot (LR) of fruit and Phytophthora crown rot (PhCR) in strawberry. LR occurs sporadically but can cause up to 70% fruit loss when weather is conducive. In Florida's annual strawberry winter production system, PhCR can be severe, resulting in plant stunting, mortality, and severe yield loss. Azoxystrobin is labeled for control of LR but not for PhCR. The aims of this research were to determine the sensitivity of P. cactorum and P. nicotianae isolates from strawberry to azoxystrobin and to investigate mechanisms of quinone-outside-inhibitor resistance present in P. cactorum and P. nicotianae based on the known point mutations within the cytochrome b (cytb) gene. Isolates of both Phytophthora spp. causing LR and PhCR were collected from multiple strawberry fields in Florida between 1997 and 2020. Isolates were tested for sensitivity to azoxystrobin at 0, 0.01, 0.1, 1.0, 10, and 50 μg/ml on potato dextrose agar amended with salicylhydroxamic acid (100 μg/ml). Isolates were separated into two groups - sensitive isolates with the 50% effective concentration (EC50) values <1.0 μg/ml, and resistant isolates having EC50 values >50 μg/ml. P. cactorum and P. nicotianae resistance to azoxystrobin was found for isolates collected after 2010. The first 450 nucleotides of the mitochondrial cytb gene were sequenced from a selection of resistant and sensitive isolates of both species. The G143A mutation reported to confer resistance to azoxystrobin was found in all resistant P. cactorum isolates. However, in P. nicotianae, qualitative resistance was observed, but the isolates lacked all the known mutations in the cytb gene. This is the first report of resistance to azoxystrobin in P. cactorum and P. nicotianae